Measuring the level of functional harmony of the members of the teaching bodies in the colleges of physical education and sports science in the southern region - Shaker Rashed, Firas; Sami Shahid, Bassem (Journal of Neonatal Surgery, 2025)
The study aimed to develop, standardize, and apply a scale for the level of job harmony among faculty members in the College of Physical Education and Sports Sciences in the Southern Region. It also aimed to identify the level of job harmony among faculty members in the College of Physical Education and Sports Sciences in the Southern Region and derive criteria and standard levels for job harmony among faculty members in the College of Physical Education and Sports Sciences in the Southern Region. The researcher adopted a descriptive approach using a survey method, correlational relationships, and normative studies to suit the nature of the problem and achieve the research objectives. The research population consisted of (420) faculty members in colleges of physical education and sports sciences in the Southern Region of Iraq. The sample was selected intentionally, consisting of (210) employees, representing (50%) of the research population. The study came out with the following most important conclusions: The scale designed by the researcher has the ability to measure the level of functional harmony among faculty members in the faculties of physical education and sports sciences in the southern region. The functional harmony scale showed that his sample was at a good level. The researcher recommended that the functional harmony scale be adopted on other samples.